Pemikiran Siti Musdah Mulia dan Yusuf Qardhawi tentang Konsep Adil dalam Poligami - Khofifah Lutfia Effendi; Zakiyatul Ulya (Sekolah Tinggi Agama Islam Negeri Majene, 2023)
Polygamy is a topic that is still being debated, especially among ulama, including between Siti Musdah Mulia and Yusuf Qardhawi. Both of them have different thoughts regarding the concept of justice in polygamy. This article aims to find out the Islamic legal analysis of the thoughts of these two figures and their comparisons. The type of research used is library research using documentation techniques in extracting data as well as descriptive analysis and comparative studies as analysis techniques. The research results show that Siti Musdah Mulia's thoughts are more in line with contemporary Islamic jurisprudence scholars because they both state that justice in polygamy is not only in the material aspect but also the immaterial. This is different from Yusuf Qardhawi's thoughts, which are more in line with classical jurisprudence scholars because they both state that justice in polygamy is only in the material aspect. The similarity of thought between the two lies in the basic istinbath used, namely surah Al-Nisā' verses 3 and 129 and the hadith narrated by Abu Hurairah. The difference lies in the type of justice that must be fulfilled in polygamy. Siti Musdah Mulia stated that justice is not only material but also immaterial which is impossible for humans to realize so this is the basis for prohibiting polygamy. In contrast to Yusuf Qardhawi who stated that justice is only material because immaterial justice is beyond the limits of human capabilities so it is not mandatory to fulfill it.